2020
DOI: 10.1177/0964528419889636
|View full text |Cite
|
Sign up to set email alerts
|

The selection of dermatomes for sham (placebo) acupuncture points is relevant for the outcome of acupuncture studies: a systematic review of sham (placebo)-controlled randomized acupuncture trials

Abstract: Background: Many randomized controlled trials (RCTs) of acupuncture reveal no significant differences between acupuncture and so-called placebo acupuncture. There is a strong tendency to replace the term “placebo” by the term “sham,” because any needling stimulates a certain physiological response. However, neither concept accounts for the great diversity of results in RCTs comparing verum acupuncture and sham (placebo) acupuncture. Some trials have shown little or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…This review found that different SA types also have distinct brain responses. The overlapping dermatomes between nonacupoints and verum acupoints may explain this phenomenon, as the segmental structure of the body and its interconnected reflex system offers neurophysiological effects [85]. Therefore, the selection of proper SA is critical in determining the efficacy of acupuncture.…”
Section: Factors Associated With the Brain Plasticity Ofmentioning
confidence: 99%
“…This review found that different SA types also have distinct brain responses. The overlapping dermatomes between nonacupoints and verum acupoints may explain this phenomenon, as the segmental structure of the body and its interconnected reflex system offers neurophysiological effects [85]. Therefore, the selection of proper SA is critical in determining the efficacy of acupuncture.…”
Section: Factors Associated With the Brain Plasticity Ofmentioning
confidence: 99%
“…However, a recent review indicates that sham acupuncture and verum acupuncture have almost identical efficacy when the dermatomes that are stimulated highly overlap. 74 The present study may help to test these authors' arguments. Because the pain of patients with BC is so severe that they can tolerate fNIRS imaging for only a short time, acupuncture with a short-time needle retention time (10 min and 30 s) will be chosen after the pilot study.…”
Section: Discussionmentioning
confidence: 76%
“…This may be explained by similar segmental innervations in HC. As shown by a recent systematic review (Ots et al, 2020 ), VA and SA have similar therapeutic effects due to their position in overlapping dermatomes, which partly explain several previous clinical studies (Assefi et al, 2005 ; Hinman et al, 2014 ) that showed no significant difference in the effect of VA compared with SA. Thus, to obtain reliable results, the location of the needles selected for SA should be at non-overlapping cutaneous segments based on the knowledge of segmental anatomy.…”
Section: Discussionmentioning
confidence: 81%